Taking a closer look at blended learning activities in a paragraph writing course - Anggri Muhtia; Suparno Suparno; Sumardi Sumardi (Informascope, 2019)
Blended learning has been talked about a lot in contemporary higher education and seen as the perfect solution for improving the quality of learning. In spite of the widespread support of acceptance this approach has gained, it is admitted that there is no single standard formula for a successful blended learning program, and thus more cases of blended learning need to be reported. This paper reports a study of the implementation of blended learning in a paragraph writing course with the aims of taking a closer look at the blended learning activities carried out in the course and revealing the responses of the students about the activities. This case study involved one lecturer and six student participants from the paragraph writing class, which were selected purposively. Data were collected through interviews, observations, and document analysis. The findings showed that there were five main learning activities in face-to-face instructions and five activities online. These activities were intended to maximize the use of classroom time for active and collaborative learning activities, supplemented with online activities to reinforce learning undertaken in the classroom. In general, student responses to blended learning activities in the paragraph writing course were positive.